Analisis Faktor-Faktor Yang Mempengaruhi E-Loyalty Dengan E-Satisfaction Sebagai Intervening Pada Nasabah Livin’ By Mandiri - Ikhsan Mawardi; Osly Usman; Ayatulloh Michael Musyaffi (KOLONI, 2024)
This research was conducted to determine the influence of e-service quality, e-trust, and e-CRM on e-loyalty with e-satisfaction as an intervening for customer Livin' by Mandiri. This research uses quantitative methods with survey instruments. Data collection was carried out using a non-probability sampling technique, namely purposive sampling, by taking a sample of 204 respondents domiciled in Jakarta who had used Livin' by Mandiri at least three times in the last six months and had experienced problems during use. Then the respondents' answers were processed using the Structural Equation Modelling Partial Least Square (SEM-PLS) method using SmartPLS 4.0 software. From hypothesis testing in this research, results were obtained that prove 1) e-service quality has an effect on e-satisfaction, 2) e-trust has an effect on e-satisfaction, 3) e-CRM has an effect on e-satisfaction, 4) e-satisfaction has an effect on e-loyalty, 5) e-service quality has an effect on e-loyalty, 6) e-trust has an effect on e-loyalty, 7) e-CRM has no effect on e-loyalty, 8) e-service quality has an effect on e- loyalty through e-satisfaction, 9) e-trust influences e-loyalty through e-satisfaction, and 10) e-CRM influences e-loyalty through e-satisfaction.